Finance as a 'forgotten technological capability' for promoting African local pharmaceutical manufacture. (1st June 2013) - Banda, Geoffrey
Finance capability as a firm-level technological capability has been neglected in debates on financing of increased sub-Saharan Africa local pharmaceutical drug manufacture, as it has in industrial development more generally. Finance capability has to date not been explicitly included in firm-level technological capabilities. Access to finance for African local pharmaceutical manufacture is not just about getting money. There are technological capabilities and complexities surrounding access to finance. Specifically for African pharmaceutical manufacture, there is little theorization and engagement with the specialist and knowledge-intensive capabilities needed by pharmaceutical firms and financial institutions. Based on fieldwork on the financing of antiretroviral drug manufacture in Zimbabwe in 2011, and interviews with pharmaceutical and financial institutions' executives up to 2013, this article sets out to better understand financial capability development, especially skills, knowledge and learning by doing. This research generates empirical data on finance capability and uses it to extend theory on technological capability, and suggests how such inclusion can improve the firm-level technological capability framework.